2008
DOI: 10.2471/blt.07.043489
|View full text |Cite
|
Sign up to set email alerts
|

Methods of suicide: international suicide patters derived from the WHO mortality database

Abstract: Objective Accurate information about preferred suicide methods is important for devising strategies and programmes for suicide prevention. Our knowledge of the methods used and their variation across countries and world regions is still limited. The aim of this study was to provide the first comprehensive overview of international patterns of suicide methods. Methods Data encoded according to the International Classification of Diseases (10th revision) were derived from the WHO mortality database. The classifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

20
374
9
29

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 470 publications
(449 citation statements)
references
References 30 publications
(1 reference statement)
20
374
9
29
Order By: Relevance
“…The great majority of suicide deaths in this study were males, with male -female ratio of 7:1. This is similar to studies that found the male gender to commonly commit suicide by hanging [21][22][23][24][25].…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…The great majority of suicide deaths in this study were males, with male -female ratio of 7:1. This is similar to studies that found the male gender to commonly commit suicide by hanging [21][22][23][24][25].…”
Section: Discussionsupporting
confidence: 77%
“…For any individual to successfully commit suicide by hanging no matter the geographical location or level of education, access to a ligature is an important factor that leads the person to suicidal action [25,26]. In this study victims committed suicide using every day common items such as; ropes, belts, electric cables, sponge and cloths.…”
Section: Discussionmentioning
confidence: 99%
“…Los factores de riesgo asociados al suicidio son variados, pero destacan entre otros las enfermedades mentales, el alcoholismo, el abuso de drogas, las enfermedades crónicas, desajustes emocionales y violencia 3 .…”
unclassified
“…the abandonment of one common method of self-harm and its substitution with another method) has not been widely reported. Although, as in many developing countries, pesticide poisoning is a major cause of death in Sri Lanka, 8,13 medicinal drugs were found to be the commonest substances used by the self-poisoning patients investigated at a tertiary care hospital in the city of Colombo in 2007. 14 We set out to investigate recent changes in the methods of self-harm in Sri Lanka -particularly the changes in the methods employed by people attempting suicide -and to explore if such changes could explain the substantial decline in suicide rates.…”
Section: Introductionmentioning
confidence: 99%